An Analysis of Abbreviation in Twitter Status of Hollywood Pop Singers - Indah Dwi Pratiwi; Leni Marlina (English Language and Literature, 2020)
Abbreviation is the process of cutting one word, some parts of the word and the combination of words into words in the new form. Abbreviation is used by all kinds of people who share situations of interests and it is often used in informal situation. The use of abbreviation is not only found in daily conversation, discussion, or speech, but also found in online interaction in social media. This study aims to find out the types and the meaning of abbreviation words and types internet language in Twitter used by Hollywood pop singers. This research used Schendl (2001) and Weakly (2006) theories about five types of abbreviation words. This study is descriptive qualitative research. The data were taken from tweets that have been posted by Hollywood pop singers on June 2019. The result showed that from 47 data that have been collected, there were four types out of abbreviation that have been found from five types of Schendl an Weakly abbreviations. They are clipping (14,9%), initialism (34,0%), blend (10,6%), contraction (40,4%) and acronym is not found from the data. From the finding it can be concluded that the type of abbreviation which is dominantly used by the singers in Twitter is contraction.